Kehadiran Komponen Cadangan (KOMCAD) Dalam Pertahanan Negara: Implementasi Operasi Militer Selain Perang (OMSP) - Sudaryono, Sudaryono; Manurung, Hendra; Pannyiwi, Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The urgency of utilizing reserve components in the Total People's Defence and Security System (Sishankamrata) in Indonesia is increasingly relevant considering the vast territorial area and the complexity of future threats, from conventional military threats to natural disasters and terrorism. National defence is a form of national defence that should be maintained by the entire Indonesian nation. However, considering the limited budget and active military personnel, empowering reserve components is a strategic solution to maintain national preparedness without burdening the state budget excessively. The purpose of this study is to analyse the extent to which reserve components play a role in the national defence system and to identify emerging challenges and opportunities. This study uses a qualitative approach with an exploratory method. Data collection was carried out through data triangulation which included defence policy analysis, literature review, and semi-structured interviews with defence experts and military personnel. Data analysis used thematic analysis to identify patterns and relevance of the main themes. A comparative study was conducted by comparing the implementation of reserve components in other countries, in order to find good practices that can be adapted in the Indonesian context. The results of the study show that reserve components are not only effective in the context of budget efficiency, but also play a role in organizing non-military operations, such as: natural disaster management and supporting the implementation of domestic security operations. In conclusion, the reserve component plays a significant role in strengthening National Defence, but supporting policies related to improving training infrastructure, empowering public awareness, and generating people participation are still also needed.